Structural analysis for the pneumatic erection of elastic gridshells. (December 2020) - Quinn, Gregory
Abstract: Elastic gridshells are celebrated for their striking biomimetic curves, long spans and efficient material usage. They are efficient in their built state but their established erection methods (using cranes, jacking towers or scaffolding) are associated with substantial complexity, cost and time which inhibit their adoption. The pneumatic erection of elastic gridshells offers a novel solution which aims to alleviate such drawbacks. A holistic approach, tackling design, computation and fabrication in unison, was necessary to realise this novel erection method. This paper focuses on the computational methods developed for the structural design and analysis of two full-scale prototypes. Findings relate to the method's scope of feasibility, suitable shapes and sizes, 'trigger' pressures required, erection sequence and identification of material suitability and performance criteria.